Expression of p53 and Cyclin D1 in oral squamous cell carcinoma and normal mucosa: An Immunohistochemical study - Swaminathan, Uma (Medknow Publications & Media Pvt Ltd, 2012)
AIM: To assess p53 and Cyclin D1 expression using Immunohistochemistry in normal mucosa and oral squamous cell carcinoma. MATERIALS AND METHODS: Twenty cases of Oral squamous cell carcinoma (OSCC) and 10 normal mucosa were used and the primary antibodies used were p53 (DAKO-DO7) and Cyclin D1 Mouse Anti human Cyclin D1 (DCS-6) 1: 100 dilution. Statistical analysis: Labelling index was calculated and mean LI and SD were calculated, using Descriptive Statistics and t-test was used to compare mean LI between antibodies used in OSCC. Percentage positivity was done by Chi-Square test. Comparison of LI between p53 and Cyclin D1 was studied using t test. RESULTS: p53 was positive in 30% and Cyclin D1 in40% of normal cases and 65% and 95% of OSCC were positive for p53 and Cyclin D1 respectively. Mean LI of p53 and Cyclin D1 were found to be statistically significant between the normal mucosa and OSCC. The correlation of mean LI of p53 and Cyclin D1 in OSCC was found to be statistically significant. LI of p53 was found to be higher than Cyclin D1 in OSCC. CONCLUSION: In the present study, increased p53 and Cyclin D1 expression were seen in OSCC when compared to the normal mucosa and a positive correlation was seen between increased p53 and Cyclin D1 expression in OSCC.